From research on friendship. Social competencies and the quality of friendship relations - Prusiński, Tomasz (Studia Psychologica: Theoria et praxis, 2017)
Friendship is a universal interpersonal relationship and is important in an individual’s social life or mental health. Previous empirical studies and theoretical considerations suggests that social competencies are correlated with friendship. The study focuses on finding and describing correlations between social competencies and the quality of friendship relations among young adults. Results of the empirical research allow to derive some important conclusions. Studies have assessed that individuals which are socially competent in a some dimension have the high quality of friendship relations.